Inhibition of tumor cell glutamine uptake by isolated neutrophils. - Learn, D B; Thomas, E L (The Journal of Clinical Investigation, 1988)
Antitumor activity of phorbol myristate acetate-(PMA) stimulated neutrophils was measured against CCRF-CEM cells. Neutrophils and tumor cells were incubated (a) as a suspension with continuous mixing to maximize the availability of oxygen or (b) after centrifugation as a pellet to maximize cell-cell contact. The cells were then incubated briefly as a suspension with [14C]glutamine under conditions that blocked further damage to the tumor cells. When cells were incubated as a suspension, inhibition of tumor-cell glutamine uptake was mediated by the myeloperoxidase/hydrogen peroxide/chloride system of stimulated neutrophils. Inhibition was blocked by adding catalase, an inhibitor of myeloperoxidase, or compounds that scavenge hypochlorous acid or chloramines. When cells were incubated as a pellet, a portion of the inhibition could not be blocked in this way, indicating that a nonoxidative mechanism contributed to inhibition. In both systems, inhibition of glutamine uptake was rapid and was obtained at effector-cell/target-cell ratios as low as 0.5:1. This inhibition was obtained under conditions that did not result in 51Cr release from cells labeled with [51Cr]-chromate, indicating that inhibition of glutamine uptake measured cytotoxicity rather than cytolysis. 51Cr release was observed only when cells were incubated together for an hour or more as a pellet at high E/T ratios. This cytolysis was mediated by the myeloperoxidase system, and a nonoxidative contribution to cytolysis was not observed. The results indicate that stimulated neutrophils are potent antitumor effectors cells when cytotoxicity rather than cytolysis is the measure of activity. Because glutamine is required for growth of many tumor cells, inhibition of glutamine uptake may represent a significant tumoristatic or tumoricidal effect.